2015
DOI: 10.1097/brs.0000000000000995
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Major Non-neurological Complications in 105 Patients Undergoing Posterior Vertebral Column Resection Procedures for Severe Rigid Deformities

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Wang and colleagues described that PVCR is a reconstruction of the trunk of the body which contains the heart, great vessels, and respiratory organs. It is reported that respiratory-related complications are more frequent, because severe spinal deformity is often associated with respiratory function impairment [ 24 ]. We were able to identify that 12.1% of the total complications related to an internal organ (5.6% were respiratory complications).…”
Section: Discussionmentioning
confidence: 99%
“…Wang and colleagues described that PVCR is a reconstruction of the trunk of the body which contains the heart, great vessels, and respiratory organs. It is reported that respiratory-related complications are more frequent, because severe spinal deformity is often associated with respiratory function impairment [ 24 ]. We were able to identify that 12.1% of the total complications related to an internal organ (5.6% were respiratory complications).…”
Section: Discussionmentioning
confidence: 99%
“…According to a review of the literature, our group found that the prognostic factors related to AL could generally be divided into the following 4 categories: patient-related factors, symptomatic factors, radiographic factors, and surgical factors. [1][2]5,[7][8]10,12,14,19,25 Currently, with the routine use of MRI and CT, fractures or nonfusion of the facet joints can be detected at an early stage, which can facilitate the accurate diagnosis and the assessment of prognostic related to the outcomes of AL. [16][17]19,24 Chang et al 25 in AS in relation to JOA recovery rate.…”
Section: Discussionmentioning
confidence: 99%
“…For patients treated with surgery, the average JOA score was 9.1 ± 1.5 (range 5.5-14) on admission and 13.2 ± 2.2 (range 7. [5][6][7][8][9][10][11][12][13][14][15][16][17] at the final follow-up. In the conservative treatment group, the average JOA score was 11.5 ± 2.9 (range 6.5-14) on admission and 12.1 ± 0.8 (range 8.5-16) at the final follow-up.…”
Section: Joa Scorementioning
confidence: 99%
“…Currently, spinal kyphosis is primarily treated with osteotomy and posterior fusion (Wang et al 2015, Zhou et al 2018, Hua et al 2019, Zhang et al 2019. However, performing a vertebral osteotomy via a posterior approach is difficult when a kyphosis is "folded" or the lumbar spine is collapsed.…”
Section: Why Was Hpt Necessary For the 3 Patients?mentioning
confidence: 99%